Pengembangan Knowledge Management System dengan Teknik Information Retrieval - Try Atmaja Linggan Jaya; Mewati Ayub (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Useful data sets can be used as information to solve problems or share knowledge with others. In the case of companies implementing the new system, many input errors, or not knowing the workflow of the program, are experienced repeatedly by the same person or people in the same department. Besides that, with the entry of new employees, it takes time to adapt and how to solve the problem. To solve it, a place is needed to record problems and their solutions, or share knowledge, both for old and new employees as 'First Aid'. Knowledge Management System application is expected to help solve the problems as a place to collect data which contains errors, cause and solving; business flow; user authorization; etc. The data used, using data from a collection of tickets, personal messages or e-mail, and knowledge owned by the user, will be entered into the database as a storage place for knowledge. In the input process, each word will be broken down based on the character 'space', tokenizing, filtering, and VSM and then entered into the database. Users can search for information or knowledge by entering keywords or sentences according to user needs, then the input will be processed by tokenizing, filtering, and calculating the length using VSM. After getting the input length, the results will use the TF-IDF algorithm and cosine similarity, and the system will display the results in list form and see the details if the results from the list are selected.